International Solidarity Fund - Spanish Relief Committee : inter-departmental correspondence - Adam, Miss
028-0142-001 I.C.3. TRADES UNION CONGRESS GENERAL COUNCIL. INTER-DEPARTMENTAL CORRESPONDENCE. From: Miss Adam To : Sir Walter Citrine Department : Women's Date : 14th December, 1936. SUBJECT. International Solidarity Fund - Spanish Relief Committee. I had a chat with Mary Sutherland on Saturday morning. The Amount collected to date is £168.17.10d. Roughly about £120 has been spent on wool which is now being knitted. Knitting parties are at work. Press. Mary tells me that a further appeal was forwarded to the Press including the "New Statesman" and "Time and Tide". Curiously enough the "New Statesman" and "Time and Tide" refused to advertise our appeal. 292/946/28/142